Investigation and Analysis on Litchi Germplasm Resources in Lanxi, Zengcheng, Guangdong Province - Yancong FENG; Na JI; Boxuan NIE; Shuai LIU; Zhanhui ZHANG; Minglei ZHAO; Meijing LIAO; Jianguo LI (Guangdong nongye kexue, 2023)
【Objective】Zengcheng has a long history of planting litchi, and is one of the high-quality litchi producing areas in Guangdong, therefore it is of great significance to systematically collect, identify and evaluate their germplasm resources.【Method】A systematically investigation was conducted on the local litchi resources and ancient litchi resources in six villages in Zengcheng District, Guangzhou, Guangdong Province.【Result】Information of a total of 160 individual plants was collected, including 45 litchi seedlings, and the fruit characters of 26 fruiting trees were analyzed and evaluated. The results showed that the seeds of litchi seedlings were mostly full, with low wilted-nut rate (below 25%), low edible rate (below 75%), sour taste and morerately small fruits. However, six representative litchi germplasm resources with high specificity or comprehensive quality were screened out, and their fruits had the characteristics of high wilted-nut rate (93%), long tree-keeping period, early ripening period, purple peel, strong fragrance and special taste, indicating that there were germplasm resources with excellent comprehensive characteristics and specificity in Zengcheng, Guangdong. In regard to the investigation of ancient trees, 18 representative sample sites were selected for systematic investigation, and biological characteristics of 115 ancient litchi trees were collected, and their habitat distribution characteristics and productivity were analyzed. The results showed that the fruit types of ancient trees are relatively single, and the main high-quality varieties were 'Nuomici', 'Guiwei' and 'Huaizhi'. The maximum height of the tree was 25 m, the average height was 9.8 m, the maximum trunk girth was 410 cm, the average trunk girth was 220 cm, and the average crown width was 11.5 m× 12.0 m from north to south. It was speculated that the ages of ancient litchi trees in Lanxi, Zengcheng were mostly between 100 years and 500 years, and the oldest was not more than 1 000 years. The ancient trees showed good yield performance, and the yields distributed in the downhill foothills and plains were high, most with 100 kg, up to a maximum of 300 kg.【Conclusion】Based on the investigation of litchi germplasm resources in Lanxi, Zengcheng, Guangdong Province, six specific or excellent seedling litchi germplasm resources are identified and evaluated according to their fruit characteristics, and the survival status and age of ancient litchi resources are analyzed, and relevant suggestions on resource protection and utilization are put forward. The research results can provide references for exploration and innovative application germplasm resources in Zengcheng, Guangdong Province.